Gross split production sharing contracts in the oil and gas business creating imbalance and in justice - Rani Fadhila Syafrinaldi; Toto Tohir Suriaatmadja; Chepi Ali Firman (Goodwood Publishing, 2026)
Purpose: This study examines the implementation of Gross Split Production Sharing Contracts (PSCs) in Indonesia’s upstream oil and gas sector, with particular attention to whether the allocation of rights, obligations, and risks reflects the principles of balance and fairness in contract law. Research/methodology: The research adopts a normative juridical approach using qualitative analysis. Secondary legal materials are analyzed, including oil and gas legislation, government and ministerial regulations, and the contractual provisions of Gross Split PSCs. The analysis focuses on contractors’ obligations related to signature bonuses, firm commitments, and operating costs. Results: The findings indicate that Gross Split PSCs place excessive financial, operational, and technological burdens on contractors, while the government bears minimal risk. Contractors are fully responsible for signature bonuses, firm commitments, and operating costs without cost recovery mechanisms. This contractual structure creates an imbalance of rights and obligations and contributes to contractors’ difficulties in fulfilling firm commitments and achieving agreed production targets. Conclusions: Gross Split PSCs, as currently regulated, do not adequately uphold the principles of balance and fairness. The unequal distribution of risks and obligations undermines contractual justice and the sustainability of upstream oil and gas operations. Limitations: This study is limited to normative legal analysis and does not include empirical field data. Contribution: This research provides theoretical insight into the application of balance and fairness principles in energy contracts and offers practical considerations for improving the Gross Split PSC framework.